Impact of Social Media on Self-Esteem - Jan, Muqaddas; Soomro, Sanobia Anwwer; Ahmad, Nawaz (European Scientific Journal, ESJ, 2017)
Social media has gained immense popularity in the last decade and its power has left certain long-lasting effects on people. The upward comparisons made using social networking sites have caused people to have lower self-esteems. In order to test the hypothesis 150 students from institute of business management were surveyed through questionnaires and interviews. This research was limited to the students of IoBM and Facebook, being the most popular social networking site was used as the representative of social media. Correlation and regression model was applied to the data with the help of SPSS statistics to test the relationship between social media and self-esteem. The major findings suggest that approximately 88% people engage in making social comparisons on Facebook and out of the 88%, 98% of the comparisons are upward social comparisons. Further this research proves there that there is a strong relationship between social media and selfesteem. Increase in social media usage causes the self-esteem of individuals to decrease. One hour spent on Facebook daily results in a 5.574 decrease in the self-esteem score of an individual.